Successful live birth of a healthy infant by preimplantation genetic testing for aneuploidy in a couple with recurrent spontaneous abortion: a case report - Zhu, Yuqin; Mai, Zhuoyao; Li, Ruiqi; Liao, Zaowen; Ouyang, Nengyong; Chen, Hui; Zhao, Haijing (Frontiers in Reproductive Health, 2025)
Recurrent spontaneous abortion (RSA), characterized by the occurrence of three or more pregnancy losses prior to the 28th week of gestation, stands as a formidable challenge in the realm of assisted reproductive medicine, presenting significant difficulties in both clinical diagnosis and treatment. In recent years, there has been a discernible upward trend in the incidence of RSA, and its etiology is multifaceted and intricate. Pinpointing the root causes of RSA remains an arduous task that urgently demands resolution within the field of reproductive medicine. Through a comprehensive and in-depth analysis of the RSA-related case report, embryonic chromosomal abnormalities were identified as the highest-risk factor. Utilizing preimplantation genetic testing for aneuploidy (PGT-A) technology, an euploid blastocyst was selected for transfer, which led to successful pregnancy and healthy birth. This case holds significant reference value for the clinical treatment of RSA.